Molecular-scale polysiloxane-crosslinking hydrophobic coating boosting high-performance Ni-rich cathode in damp-heat environment - Mu, Yue; Ming, Hai; Chen, Xuefang; Zhang, Songtong; Zhu, Xiayu; Zhang, Wenfeng; Cao, Gaoping; Qiu, Jingyi (Electrochimica acta, 2023)
Ni-rich layered oxide, one of the most promising cathode materials for lithium-ion batteries (LIBs) with high energy density, is suffering from the intrinsic hypersensitivity to moisture and acid gas (CO2, SO2, etc.) in the environment, leading to the generation and growth of residual lithium compounds (e.g. Li2CO3), accompanied by surficial phase transition, high alkalinity and electrochemical deterioration. Eliminating these negative effects would require considerable energy and manpower, which hinders the promotion of Ni-rich cathode materials. Herein, we introduced crosslinked poly-methylhydrosiloxane (PMHS) and hydroxy‑terminated poly-dimethylsiloxane (denoted as PDMS-OH) hydrophobic film to in situ coat single-crystal LiNi0.8Co0.1Mn0.1O2 (NCM811), isolating its Ni-rich electrode surface from moisture and acid gas to prevent side reactions. Specifically, the desired crosslinking layer, which is optimized by increasing the relative content of PMHS and decreasing the absolute content of PDMS-OH, endows the coated NCM811 with an appreciable improvement in hydrophobicity and storage performances and effectively suppresses the formation and growth of residual lithium compounds on the surface of NCM811 particles in a simulated damp-heat storage environment. Simultaneously, the crosslinked coating diminished the extraction of Li and Ni during exposure and maintained the high electrochemical performance of NCM811. This proposed strategy to crosslink polysiloxane film on the surface of Ni-rich cathode materials greatly alleviates the problem of storage failure, which will promote the practical popularization of Ni-rich cathode materials in LIBs. In situ crosslinked polysiloxanes coating layer endows surface of Ni-rich oxide cathode material with appreciable and durable hydrophobicity, successfully improving the ability of Ni-rich oxide cathode to resist severe environments and preventing electrochemical deterioration from side reactions induced by H2O or other acid gasses. [Display omitted]